Innovative Arduino-Based Arabic Learning Tool for Early Childhood Education - Rizkyaturrohma, Alifiyah; Hikmah , Khizanatul (Indonesian Journal of Islamic Studies, 2024)
This study explores the integration of Arabic language learning into the PAUD curriculum, leveraging the critical phase of early childhood brain development. Employing the versatile Arduino Mega hardware, designed for microcontroller-based applications, researchers developed a tailored Arabic learning tool using the Addie r&d model method. The tool features a playful monkey character, equipped with an Arabic vocabulary drawing board, with vocabulary selection tailored to student development. Research methods encompassed interviews, observations, and questionnaires, yielding material validation test results of 100% and media validation test results of 89%. This research offers a valuable contribution in the form of a student-centric Arduino-based Arabic learning tool, poised to enhance Arabic language acquisition in early childhood education. Highlight: Integration of Arabic language learning in early childhood education capitalizes on critical stages of brain development. Utilizing Arduino Mega hardware, researchers employ the Addie r&d model to create a customized Arabic learning tool featuring an engaging monkey character. Validation tests demonstrate high effectiveness, with material validation scoring 100% and media validation reaching 89%, offering a promising contribution to Arabic language acquisition in early childhood education. Keyword: Arabic Language Learning, PAUD Curriculum, Early Childhood Education, Arduino Mega Hardware, Student-Centric Learning Tool